Experimental Study on Bending Performance of Prefabricated Retaining Wall - Yidan Ma; Hengchen Du; Shicheng Nie; Kai Zhu; Han Liu; Dehong Wang (Buildings)
To address the engineering issues of difficult quality control, complex construction processes, and long construction periods in cast-in-place protective walls for manually excavated piles, a prefabricated protective wall structure is proposed. This study aims to investigate its mechanical properties and key influencing parameters through experiments. Six groups of prefabricated wall segment specimens with different wall thicknesses (50 mm, 65 mm) and concrete strengths (C50 concrete, reactive powder concrete RPC) were designed, and two-point bending tests were conducted to systematically analyze their failure characteristics, crack development patterns, and strain distribution laws. The test results show that the peak vertical bending displacements at mid-span of the specimens are 11–18 mm (1.83–2.71% of the radius). The 65-mm-thick specimens exhibit 3–10% higher flexural strength than the 50-mm-thick ones, and reactive powder concrete (RPC) specimens of the same thickness show an 8.3% increase in strength compared to C50 concrete specimens. When the load reaches 80% of the ultimate load, abrupt changes in concrete strain occur at the mid-span and loading points, while the strain at the fixed end is only 15–20% of the mid-span strain. The prefabricated protective wall demonstrates superior deformation resistance, with vertical displacements (3–5% of the radius) significantly lower than those of cast-in-place walls. This research clarifies the influence of wall thickness and concrete strength on the mechanical properties of prefabricated protective walls, providing key mechanical parameters to support their engineering applications.